Health benefits of astaxanthin and its encapsulation for improving bioavailability: A review - Beifang Li; Ji-Young Lee; Yangchao Luo (Journal of Agriculture and Food Research, 2023)
As a carotenoid originally used as a pigment in the aquaculture industry, astaxanthin is gaining interest in food, nutritional, and biopharmaceutical sciences in recent years due to its great antioxidant and anti-inflammatory properties, as well as its health effects on diabetes, cardiovascular diseases, cancer, and so on. However, the poor chemical stability and water solubility make practical applications of astaxanthin on human health become challenging. Nanoencapsulation of astaxanthin is considered a possible solution to tackle such challenges by improving chemical stability, and providing controlled release, thus enhancing its bioaccessibility and bioavailability. In this article, an updated overview of the chemistry, sources, and extraction methods of astaxanthin is provided. Moreover, recent studies on the health effects of astaxanthin were introduced and then the recent progress on the preparation of various nanoparticles for the encapsulation of astaxanthin are highlighted. This perspective article aims to provide guidance on potential structural designs of nanoparticles for the encapsulation of astaxanthin and the effects of nanoencapsulation on its functionality.